DETERMINATION OF IN VITRO ANTIPROLIFERATIVE EFFECT OF THREE IMPORTANT CEROPEGIA SPECIES ETHANOLIC EXTRACTS ON CULTURED HCT-118 CELL LINES - BINISH T; MARY SUJA R (International Journal of Pharma and Bio Sciences, 2015)
Bio prospecting of plants with anti-proliferative activity has been a major focus on the search of plants based cure. The pharmacological importance of Ceropegia species (Apocynaceae) is mainly due to the presence of a pyridine alkaloid ‘Ceropegin’ a potential antipyretic, analgesic, local anesthetic, antiulcer, mast-cell stabilizing, hepato-protective, tranquilizing, and hypotensive. Use of plant derived compounds as potent anticancer agents is of recent research interest. In the continuing effort to screen Ceropegia species (Ceropegia spiralis, Ceropegia juncea, and Ceropegia candelabrum ) for anticancer activity, plants were collected, micro propagated and hardening. In-vitro propagated plants are collected, extracts tested for the activity using cell lines namely HCT-118 (Colon cancer cell) of the extracts from three species of same families tested (10,50,and100µg/ml). 10ug ofCeropegia spiralis showed 47.15% of cell death, which can be considered significant. Apoptosis was confirmed by acridine orange (AO) ethidium bromide (EB) fluorescent double staining which confirms the potent anticancer effect of ethyl acetate fraction of Ceropegia spiralis.